2014
DOI: 10.1002/cjoc.201400350
|View full text |Cite
|
Sign up to set email alerts
|

AgF‐Mediated Dialkylation of Activate Alkenes: An Efficient Access to Nitrile‐Containing Spirooxindoles

Abstract: A novel Ag-mediated dialkylation reaction of alkenes was disclosed, in which AgF was essential to activate C-H bond of acetonitrile. This reaction provided an efficient way to nitrile-containing spirooxindoles from readily available (1H-indol-3-yl)methanamine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A further O 18 labeling experiment (entry 7) showed that the O 18 can not be detected in the product 2a when the reaction was carried out in the presence of H 2 O 18 which was oen used to identify the source of oxygen in the product. 12 Besides, the investigation also showed that no byproduct can be observed yet when the reaction was carried out in the presence of some additional additives such as NH 3 $H 2 O (entry 8) or CH 3 OH (entry 9) respectively. These results should be crucial to demonstrate the role of DMF in the mechanism.…”
Section: Resultsmentioning
confidence: 88%
“…A further O 18 labeling experiment (entry 7) showed that the O 18 can not be detected in the product 2a when the reaction was carried out in the presence of H 2 O 18 which was oen used to identify the source of oxygen in the product. 12 Besides, the investigation also showed that no byproduct can be observed yet when the reaction was carried out in the presence of some additional additives such as NH 3 $H 2 O (entry 8) or CH 3 OH (entry 9) respectively. These results should be crucial to demonstrate the role of DMF in the mechanism.…”
Section: Resultsmentioning
confidence: 88%
“…A novel method for the synthesis of nitrile-containing spirooxindoles 5 mediated by AgF was developed by Liu and co-worker. 35 Activated alkenes 4 were dialkylated with acetonitrile as solvent, 4 equiv. of AgF as catalyst in an atmosphere of nitrogen at 110 °C in which the C–H bond of acetonitrile was activated by AgF ( Scheme 2 ).…”
Section: Ag-catalyzed Spirooxindole Synthesismentioning
confidence: 99%